2022
DOI: 10.1155/2022/7615892
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Convergence Angle of Tooth Preparations for Complete Crowns Among Dental Students: Typodont vs Simulator

Abstract: Introduction. The technology-enhanced learning and simulation-based learning are critically important pedagogic tools. They allow students to perfect their preclinical training by improving their skills and their manual dexterity while facilitating the acquisition of the know-how necessary for reproduction more realistically and faithfully of the behaviors required for a better dental practice. Retention is one of the mechanical fundamental principles of preparation of cemented fixed prostheses. It depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…At the same time, it is extremely difficult to obtain a convergence angle of 6-7° in practice without the formation of sub-insides. Thus, in various studies, both conventional and more recent, it was found that the total convergence angle of prepared teeth often exceeded the above parameters and ranged from 1 to 50° [2][3][4][5][6][7][8][9][10] . Based on this, many scientists consider it necessary to prepare teeth for the manufacture of metalceramic fixed dental prostheses with a greater convergence angle and justify it in the range of 10° to 20° [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is extremely difficult to obtain a convergence angle of 6-7° in practice without the formation of sub-insides. Thus, in various studies, both conventional and more recent, it was found that the total convergence angle of prepared teeth often exceeded the above parameters and ranged from 1 to 50° [2][3][4][5][6][7][8][9][10] . Based on this, many scientists consider it necessary to prepare teeth for the manufacture of metalceramic fixed dental prostheses with a greater convergence angle and justify it in the range of 10° to 20° [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%